Reduced superoxide dismutase-1 (SOD1) in cerebrospinal fluid of patients with early psychosis in association with clinical features - Coughlin, Jennifer M.; Leweke, F. Markus (Schizophrenia research, 2017)
Oxidative stress is implicated in the underlying pathophysiology of psychosis from studies of animal models and of tissues obtained from patients. Superoxide dismutase 1 (SOD1) is an antioxidant responsible for reducing free radicals. SOD1 levels in cerebrospinal fluid (CSF) reportedly correlate with those in brain. We hypothesized that patients in early-stages of psychotic disease may have altered SOD1 in CSF compared to healthy controls. We previously reported in a pilot study that SOD1 levels in CSF of patients with recent onset schizophrenia (SZ) were lower compared to healthy controls. Building on that work, in the present study we examined SOD1 levels in CSF acquired from two additional cohorts. Specifically, we studied SOD1 levels in CSF from a cohort of 15 patients with recent-onset psychosis and 18 healthy controls, as well as the second cohort of 18 antipsychotic-naïve patients with SZ and 20 healthy controls. In the first cohort, recent onset of illness was defined as within five years of onset of psychotic symptoms, and performance on neuropsychological testing as well as symptom severity were assessed. We observed 26.5% lower SOD1 in CSF from patients across both cohorts compared to controls (P=0.045) that was consistent with our previous report (30%). Among the cohort of patients with recent onset of SZ, SOD1 in CSF was positively correlated with composite performance on neuropsychological testing. Our results support further study of the relationship between cognitive deficits and oxidative stress in the central nervous system of patients with psychosis, including through study of SOD1.